Urine of Cats with Severe Fever with Thrombocytopenia Syndrome: A Potential Source of Infection Transmission - Hirohisa Mekata; Mari Yamamoto; Yasuyuki Kaneko; Kentaro Yamada; Tamaki Okabayashi; Akatsuki Saito (Pathogens)
Severe fever with thrombocytopenia syndrome (SFTS), caused by infection with the SFTS virus, is an emerging fatal tick-borne zoonosis endemic to East Asia. Although SFTS is a tick-borne disease, the virus can be transmitted from animals with SFTS without a tick bite. Direct transmission of the SFTS virus from animals to humans has been reported; however, the transmission route is unclear in some cases. Therefore, this study focused on the possibility of SFTS virus transmission through urine and attempted to isolate the infectious virus from the urine of animals with SFTS. Since more efficient cell isolation is needed to determine whether the SFTS virus is present, we first expressed dendritic cell-specific ICAM-3-grabbing nonintegrin (DC-SIGN), the major receptor for the virus, in Vero cells (Vero-DC-SIGN cells) using a retroviral vector. When inoculated with equal amounts of the SFTS virus strain and SFTS-virus-infected animal serum, Vero-DC-SIGN cells had 42–136% and 20–85% more foci, respectively, than their parent Vero cells. After confirming that Vero-DC-SIGN cells were more suitable for the isolation of the SFTS virus, we investigated whether it could be isolated from the urine of eight cats and two dogs with SFTS. The virus was isolated from 25 μL of urine from two cats with SFTS. Considering that cats excrete 50–100 mL of urine per day, the transmission of the SFTS virus via the urine of cats with SFTS cannot be ruled out. Individuals examining or caring for cats suspected of having SFTS should be aware of the possibility of viral transmission via urine.